2016
DOI: 10.1128/mcb.00370-16
|View full text |Cite
|
Sign up to set email alerts
|

MIST1 and PTF1 Collaborate in Feed-Forward Regulatory Loops That Maintain the Pancreatic Acinar Phenotype in Adult Mice

Abstract: bMuch remains unknown regarding the regulatory networks formed by transcription factors in mature, differentiated mammalian cells in vivo, despite many studies of individual DNA-binding transcription factors. We report a constellation of feed-forward loops formed by the pancreatic transcription factors MIST1 and PTF1 that govern the differentiated phenotype of the adult pancreatic acinar cell. PTF1 is an atypical basic helix-loop-helix transcription factor complex of pancreatic acinar cells and is critical to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 74 publications
4
48
1
Order By: Relevance
“…This observation is consistent with previous studies showing that gastric chief cells also induce Mist1 during ER stress (19), and it supports the hypothesis that transient ER stress and Xbp1s expression may be the developmental trigger that activates Mist1 within regenerating stomach crypts. This is in contrast to pancreatic acinar cells, in which developmental expression of Mist1 is achieved by the acinar transcription factor complex PTF1 (27) while the ER stress-induced enhancement of MIST1 reported here is fully dependent on XBP1. Interestingly, a modest 2-fold increase in Ptf1a expression is also observed during thapsigargininduced ER stress (unpublished results), suggesting that the PTF1 complex might play a minor role in augmenting Mist1 gene expression in ER-stressed pancreatic acinar cells.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…This observation is consistent with previous studies showing that gastric chief cells also induce Mist1 during ER stress (19), and it supports the hypothesis that transient ER stress and Xbp1s expression may be the developmental trigger that activates Mist1 within regenerating stomach crypts. This is in contrast to pancreatic acinar cells, in which developmental expression of Mist1 is achieved by the acinar transcription factor complex PTF1 (27) while the ER stress-induced enhancement of MIST1 reported here is fully dependent on XBP1. Interestingly, a modest 2-fold increase in Ptf1a expression is also observed during thapsigargininduced ER stress (unpublished results), suggesting that the PTF1 complex might play a minor role in augmenting Mist1 gene expression in ER-stressed pancreatic acinar cells.…”
Section: Discussioncontrasting
confidence: 88%
“…Thus, in the context of ER stress, the scaling effect of MIST1 is achieved by amplifying an initial transcriptional activation achieved by XBP1. This model is supported by additional findings showing that MIST1 similarly collaborates with PTF1 to jointly regulate developmental gene targets via proximal DNA binding (27). The many observations that MIST1's transcriptional activity typically produces moderate changes in gene expression levels rather than functioning as a more customary binary on/off switch support this supposition.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Thus, PTF1A and MIST1 also collaborate at target genes. Indeed, we have recently shown that PTF1A and MIST1 collaborate extensively through reiterated feed-forward regulatory loops controlling acinar genes (102). The extensive regulatory relationships show that PTF1A collaborates with the other network core factors in feed-forward control strategies at large numbers of acinar genes.…”
Section: Discussionmentioning
confidence: 99%